What happens to an acellular scar matrix after implantation in vivo? A histological and related molecular biology study. (26th November 2020) - Lai, Chenzhi; Song, Guodong; Pan, Bo; Zhao, Bo; Wang, Hongquan; Tian, Dan; Zhao, Jingyi; Du, Le; Guo, Xiaoshuang; Jin, Xiaolei; Zong, Xianlei
Abstract: It has been established that scar acellular matrices (AMs), which allow cell proliferation, have similar characteristics. The aim of this study was to investigate the repair effect of scar AMs on animals, thus providing a reference for clinical application. Selected mature and immature scar AMs were implanted into animals, and then a negative control group was set for comparison. The effect of scar AMs on wound healing was observed through tissue staining, RT-qPCR, and immunohistochemistry. The materials showed milder inflammation and faster extracellular matrix (ECM) deposition than the negative control group. The ECM deposition and new vessels increased over time. However, the arrangement of ECM in mature scar AM was more regular than in immature scar AM and the negative control group, and more new vessels grew in the mature scar AM group than in the immature scar AM group and negative control group over the same period. The transforming growth factor-β level was elevated at one month, two months, and six months. COLA1 and vimentin levels all peaked at six months. Matrix metalloproteinase and TIMP1 were also elevated at different months. Collectively, scar AMs can effectively promote wound healing and vascularization. Mature scar AMs have a better regeneration effect.